Auto Bending Machine Innovation to Improve PCB Production Control Unit - purwono, purwono; supratno, setyo; Bakri, Muhammad Amin (Journal of Energy and Electrical Engineering, 2024)
This research aims to implement the Auto Bending Lead Capacitor PCB Control Unit machine in manufacturing processes to improve operational efficiency and production capacity. The study begins with a literature review on the use of bending machines in various manufacturing industries, including integration with polarity inspection using Keyence Fiber Optic sensors. The implementation of this machine is based on kaizen and improvement initiatives for continuous improvement in production efficiency, waste reduction, and product quality enhancement. The findings show significant increases in production capacity with a time efficiency improvement of 2.87 seconds per product and monthly cost savings of Rp. 11,671,647. The Break Event Point (BEP) analysis indicates that the initial machine investment can be recouped within 2.7 months post-implementation. Recommendations for improvement include adding distance sensors for bend result detection and integrating production monitoring systems to enhance overall operational control. This research contributes significantly to improving manufacturing process efficiency through cutting-edge technology in electronic component production.